Bioinformatics in the Era of Post Genomics and Big Data 2018
DOI: 10.5772/intechopen.76051
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gene Expression by Gene Architecture and Promoter Structure

Abstract: Regulation of gene expression is achieved by the presence of cis regulatory elements; these signatures are interspersed in the noncoding region and also situated in the coding region of the genome. These elements orchestrate the gene expression process by regulating the different steps involved in the flow of genetic information. Transcription (DNA to RNA) and translation (RNA to Protein) are controlled at different levels by different regulatory elements present in the genome. Current chapter describes the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…at a well-defined location relative to the transcription initial sites. 20 The origins of replication have a similar chromatin environment and share some genetic features to that of transcription-activating sequences or promoters. 2 Mounting evidence showed that the Oris are inclined to sequence positions in the vicinity of transcriptional start sites (TSSs).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…at a well-defined location relative to the transcription initial sites. 20 The origins of replication have a similar chromatin environment and share some genetic features to that of transcription-activating sequences or promoters. 2 Mounting evidence showed that the Oris are inclined to sequence positions in the vicinity of transcriptional start sites (TSSs).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…DNA duplex stability or free energy of the fragment of DNA depends on hydrogen bonds between bases and the stacking interaction between consecutive bases and can be computed by summing the free energy of the constituent dinucleotides. 20 The melting temperature of a DNA fragment directly depends on DNA stability. A dinucleotide descriptor based on the collection of melting studies of 108 oligonucleotides 57 has been used for computing DNA stability.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BGN4+G1 exhibited the highest hydrolytic activity regardless of the incubation time, for which the enzyme activity was continuously 2.5 to 4.2 times higher than that of BGN4. Many previous studies reported that the consensus sequences (−35 and −10 regions) [38,39], spacer sequences [39,40], TG motif [41], UP elements [42] and the promoters' structural properties [43] can all affect the promoter strength. The promoters used in this study seem to differ in strength due to differences in those factors.…”
Section: Comparison Of Hydrolytic Activities Between Transformants An...mentioning
confidence: 99%